Analysis of Teaching Strategies by Teachers in Cultivating Reading Interest of Grade V Students at SDN Panongan 1 - Khalisha Salsabila; Mawardi Mawardi; Najib Hasan (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze teachers' teaching strategies in fostering reading interest among fifth-grade students at SDN Panongan 1. Teachers' strategies in cultivating reading interest are crucial as it significantly impacts students' literacy and academic development. The method employed was descriptive qualitative with data collected through observation, interviews, and documentation. Findings indicate that teaching strategies involving varied learning approaches, positive teacher-student interactions, and supportive learning environments significantly enhance students' reading interest. Additional supportive factors such as school support and parental involvement also play pivotal roles in the success of these strategies.